Studies on mononuclear chelates derived from substituted Schiff bases ligands (part 3).: Synthesis and characterization of a new 5-nitrosalicylidene-p-aminoacetophenoneoxime and its complexes with Co(II), Ni(II), Cu(II), and Zn(II) - Canpolat, E; Kaya, M (Maik Nauka/Interperiodica, 2005)
A new ligand, 5-nitrosalicylidene-p-aminoacetophenoneoxime (HL), was synthesized from p-aminoacetophenoneoxime and 5-nitrosalicylaldehyde under reflux in absolute EtOH at 60 degrees C for 3 h. Mononuclear complexes with a metal : ligand ratio of 1 : 2 were prepared with Co-II, Ni-II, Cu-II, and Zn-II salts. Their structures were determined on the basis of elemental analyses, IR, H-1 and C-13 NMR, electronic spectra, magnetic susceptibility measurements, molar conductivity, and thermogravimetric analyses. According to the results, two ligands were suggested to be coordinated to each metal atom by phenolic oxygen and imino nitrogen to form high-spin tetrahedral complexes with cobalt(II), nickel(II), and copper(II) while forming a diamagnetic complex with zinc(II).
Keywords: Transition-Metal-Complexes; Ray Crystal-Structure; Vic-Dioxime; Copper(Ii); Nickel(Ii); 2,2'-Bipyridylamine; Salicylaldehyde; Reactivity; Zinc(Ii); Cd(Ii)